Analisis Kinerja Keuangan CU Betang Asi Tempat Pelayanan (TP) Kantor Pusat Di Palangka Raya - Clarina Lorensia; Rinto Alexandro; Tonich Uda; Kuwing Baboe; Dehen Erang (FKIP, Universitas Palangka Raya, 2022)
This study aims to determine the financial performance of the CU Betang Asi TP Cooperative Headquarters in Palangka Raya during the 2016 – 2018 period. The benefit of this research is as a reference in making decisions and determining future policies, especially in the field of cooperative financial performance. The variable in this study is financial performance, with a population of all financial statement data, while the sample is the balance sheet and income statement for the period 2016-2018. Data collection uses documentation and observation techniques, while the data analysis technique used is ratio analysis based on financial performance which includes liquidity ratios (current ratio and cash ratio), solvency ratios (assets to debt ratio and debt to equity ratio), and profitability ratios (return on equity and earning power). Based on the results of research on the financial performance of the CU Betang Asi TP cooperative, Head Office in Palangka Raya during the period 2016 – 2018 from the analysis of the Liquidity ratio, it has decreased, while Solvency has developed quite well in its business activities, and the Profitability Ratio at the CU Betang Asi Palangka Raya Cooperative has experienced a decline. Decreased, but cooperatives are still good enough to be able to carry out their business activities.